THE ROLE OF PSYCHOTHERAPY IN THE GRIEVING PROCESS OF FAMILIES BEREAVED BY SUICIDE: : AN INTEGRATIVE REVIEW (PRÁXIS EM SAÚDE, 2025)
The present study consists of an integrative literature review aimed at analyzing the contributions of psychotherapy to the grieving process of families bereaved by suicide. The research sought to identify and synthesize scientific publications on the topic, with the goal of broadening the understanding of effective practices and contributing to the strengthening of more sensitive care networks. The methodology involved searches in the SciELO, LILACS, PePSIC, IndexPsi, and PsycInfo databases, using the descriptors "psychotherapy," "grief," and "suicide." Articles published between 2020 and 2025 that met the inclusion criteria were selected. The final considerations indicate that psychotherapy offers significant contributions to coping with grief after suicide, with approaches such as Internet-Based Cognitive Behavioral Therapy (ICBT) and the Two-Track Model of Bereavement (TTMB) standing out as relevant. However, the need for further research aimed at adapting and evaluating specific interventions is emphasized, in order to overcome barriers to psychosocial support for this population.
Keywords: Psychotherapy; Grief; Suicide